LEARNING MEDIA USING DISCOVERY LEARNING APPROACH TO IMPROVE STUDENT LEARNING OUTCOMES - Saut Dohot Siregar; Berkat Panjaitan; Ermi Girsang; Hotromasari Dabukke (Jurnal Pendidikan Fisika, 2019)
Learning media gives a good influence on students to understand the content of the lessons delivered by the teacher. Learning media makes students become active in learning so students do not only hear explanations from the teacher which can make students' different catches. The purpose of this research is the application of learning media in the learning process of students, and using the discovery learning model is expected to obtain an increase in student learning outcomes. This research was conducted in several 10th grade high schools in Medan, Indonesian. Sampling is done by cluster random sampling where every school has the same opportunity to become a research sample. The instrument of learning outcomes is in the form of multiple choice questions, and the instrument of student interest in learning is in the form of a questionnaire. The results of the discussion show that by using the discovery learning model with the help of instructional media can improve student learning outcomes, especially in vector material. This increase was seen from the response of students as much as 83.3% agreed to the use of media during learning. Learning media by using applications that were developed showed a positive interest in learning by students. The results of student learning instruments indicate that there are differences in the mean learning outcomes of control class students with the mean learning outcomes of experimental class students. The mean value of the control class was 53.61 while the mean learning outcomes in the experimental class was 63.66